2023
DOI: 10.3390/jcs7040173
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Thermoelectric Properties of Polypropylene Composites Melt-Processed Using Pyrograf® III Carbon Nanofibers

Abstract: The electrical conductivity (σ) and Seebeck coefficient (S) at temperatures from 40 °C to 100 °C of melt-processed polypropylene (PP) composites filled with 5 wt.% of industrial-grade carbon nanofibers (CNFs) is investigated. Transmission Electron Microscopy (TEM) of the two Pyrograf® III CNFs (PR 19 LHT XT and PR 24 LHT XT), used in the fabrication of the PP/CNF composites (PP/CNF 19 and PP/CNF 24), reveals that CNFs PR 24 LHT XT show smaller diameters than CNFs PR 19 LHT XT. In addition, this grade (PR 24 LH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
4
6
0
Order By: Relevance
“…Thus, over this interval of temperatures (30 °C–94 °C), the CNF powder presents a positive temperature effect (PTC) or dσ/dT < 0, defined as the increase in the electrical resistivity during a heating process. Notably, this matches well to the PTC found for Pyrograf ® III CNFs PR 24 LHT XT and PR 19 LHT XT [ 32 ]. From this, it can be deduced that, despite the three Pyrograf ® III CNFs (PR 24 LHT XT, PR 19 LHT XT and PR 25 PS XT) showing different structures, all of them present similar σ (T) behaviors.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, over this interval of temperatures (30 °C–94 °C), the CNF powder presents a positive temperature effect (PTC) or dσ/dT < 0, defined as the increase in the electrical resistivity during a heating process. Notably, this matches well to the PTC found for Pyrograf ® III CNFs PR 24 LHT XT and PR 19 LHT XT [ 32 ]. From this, it can be deduced that, despite the three Pyrograf ® III CNFs (PR 24 LHT XT, PR 19 LHT XT and PR 25 PS XT) showing different structures, all of them present similar σ (T) behaviors.…”
Section: Resultssupporting
confidence: 87%
“…Figure 5 and Table 2 show the experimental Seebeck coefficient of the coated textiles and as-received CNF powder at 30 °C. The CNF powder shows n-type character (−0.60 ± 0.03 μV∙K −1 ), which is in agreement with other Pyrograf ® III CNF grades (PR 24 LHT XT and PR 19 LHT XT [ 32 ]). This is not normally observed with similar carbon allotropes (e. g. CNTs) due to their p-doping with the environment [ 33 ].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The large size of the CNFs blocked the mesoporous structure of the silica aerogel and S BET dropped from 1199 to 848 m 2 ·g –1 with the addition of 0.5 wt % CNF. Meador et al observed a similar trend when incorporating up to 5 wt % of CNF (with a diameter of 100 nm and length of >100 μm) in their TMOS silica aerogels cross-linked with di-isocyanate. Lamy-Mendes et al followed two routes to modify the surface of MWCNT to achieve a better affinity between the MWCNT and silica sol: one with HNO 3 and the other with HNO 3 along with silanization.…”
Section: Resultsmentioning
confidence: 99%
“…Polypropylene is one of the most important commodity plastics used in variety of applications, among them fibers [1], composite materials [2,3], and food packaging products [4]. Commonly, additives such as stabilizers and plasticizers [4], fillers [5,6], flame retardants [1] or dyes and pigments [7,8] are incorporated into polypropylene to adjust the mechanical and processing properties and to improve appearance.…”
Section: Introductionmentioning
confidence: 99%